Tin oxide particle dispersion, and method for producing tin oxide particle laminate film
By utilizing a tin oxide particle dispersion with a controlled zeta potential, the challenges of forming a uniformly conductive tin oxide particle laminated film are addressed, achieving excellent electrical conductivity and stable film thickness for applications like perovskite solar cells.
Patent Information
- Application Number
- JP2023163348
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-08
AI Technical Summary
Forming a thin, uniform, and highly conductive tin oxide particle laminated film is challenging, especially for applications like perovskite solar cells, where the film thickness is in the nano-order and uniform conductivity is essential.
A tin oxide particle dispersion with a zeta potential of -35mV or less at pH 10 is used, which ensures uniform dispersion of tin oxide particles without aggregation, even when the dispersant volatilizes during heating, thereby maintaining excellent electrical conductivity.
This approach allows for the formation of a laminated tin oxide particle film with excellent electrical conductivity, eliminating the need for non-volatile dispersants and ensuring stable, uniform film thickness, even at nano-order scales.
Smart Images

Figure 2025054304000002 
Figure 2025054304000003 
Figure 2025054304000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a tin oxide particle dispersion liquid that can be used when forming, for example, a conductive film, and a method for producing a tin oxide particle laminated film using the tin oxide particle dispersion liquid. [Background technology]
[0002] Since tin oxide has relatively good electrical conductivity, tin oxide particle laminated films having a structure in which tin oxide particles are laminated are used as conductive materials for conductive layers in various devices, etc. In order to improve specific properties of the tin oxide particle laminated film, materials in which various elements are doped into tin oxide have also been proposed. The above-mentioned tin oxide particle laminated film is formed by applying a tin oxide particle dispersion liquid in which tin oxide particles are dispersed, and drying the same.
[0003] In the above-mentioned tin oxide particle laminated film, the number of contact points between the tin oxide particles affects the electrical conductivity, and therefore it is required to form a tin oxide particle laminated film in which the tin oxide particles are uniformly arranged. Therefore, for example, Patent Document 1 proposes a technique for forming a film by spin coating in a gas flow, in which the vapor pressure is controlled during film formation to adjust the drying speed of the dispersion liquid, thereby forming a uniform tin oxide particle laminated film. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 64-027667 Summary of the Invention [Problem to be solved by the invention]
[0005] Recently, the above-mentioned tin oxide particle laminated film has been considered for use as, for example, an electron transport layer in a perovskite solar cell. However, the electron transport layer in a perovskite solar cell has a very thin film thickness of the nanometer order, and it has been even more difficult to form a uniform film with excellent conductivity. In addition, in other devices as well, the trend toward smaller size and thinner thickness is progressing, and there is a demand for thin and uniform formation of tin oxide particle laminated films that serve as conductive layers.
[0006] In order to form a uniform tin oxide particle laminated film, it is required that the tin oxide particles are dispersed without agglomeration during the film formation process using a tin oxide particle dispersion liquid. Here, when the applied tin oxide particle dispersion liquid was heated, the dispersant contained in the tin oxide particle dispersion liquid was volatilized, and the tin oxide particles were likely to aggregate. If a non-volatile dispersant was added, the non-volatile dispersant would be present between the tin oxide particles, reducing the number of contact points between the tin oxide particles, and thus reducing the electrical conductivity.
[0007] The present invention has been made in consideration of the above-mentioned circumstances, and has an object to provide a tin oxide particle dispersion capable of forming a tin oxide particle laminate film having excellent electrical conductivity in which tin oxide particles are uniformly arranged, and a method for producing a tin oxide particle laminate film. [Means for solving the problem]
[0008] In order to solve the above problems, the present inventors conducted extensive research and discovered that by keeping the zeta potential of a tin oxide particle dispersion low in a basic solvent, the electrical repulsion between the tin oxide particles increases, the tin oxide particles are uniformly dispersed without agglomeration, and a tin oxide particle laminate film with excellent electrical conductivity can be formed.
[0009] The present invention has been made based on the above-mentioned findings, and a tin oxide particle dispersion liquid of embodiment 1 of the present invention is a tin oxide particle dispersion liquid in which tin oxide particles are dispersed in a solvent, and is characterized in that the zeta potential at pH 10 is −35 mV or less.
[0010] According to the tin oxide particle dispersion of the first aspect of the present invention, the zeta potential at pH 10 is suppressed to a low level of -35 mV or less, so that when this tin oxide particle dispersion is applied, the tin oxide particles are uniformly dispersed without agglomeration. Therefore, even if the dispersant volatilizes when the coating film of the tin oxide particle dispersion is heat-treated, the aggregation of the tin oxide particles is suppressed, and the tin oxide particles are uniformly arranged. In addition, there is no need to add a non-volatile dispersant, and the presence of the non-volatile dispersant between the tin oxide particles can be suppressed. This ensures a sufficient number of contact points between the tin oxide particles, making it possible to form a tin oxide particle laminated film having excellent electrical conductivity.
[0011] A tin oxide particle dispersion liquid of a second aspect of the present invention is characterized in that in the tin oxide particle dispersion liquid of the first aspect, the tin oxide particles are doped with a different element. According to the tin oxide particle dispersion liquid of aspect 2 of the present invention, the tin oxide particles are doped with a different element, so that the properties of the tin oxide particles can be adjusted and a tin oxide particle laminate film can be formed according to required properties.
[0012] A tin oxide particle dispersion liquid of a third aspect of the present invention is characterized in that in the tin oxide particle dispersion liquid of the second aspect, the different element is one or more elements selected from the group consisting of antimony, fluorine and phosphorus. According to the tin oxide particle dispersion liquid of aspect 3 of the present invention, the different elements are one or more selected from antimony, fluorine and phosphorus. This makes it possible to adjust the properties of the tin oxide particles and form a tin oxide particle laminate film according to required properties.
[0013] A tin oxide particle dispersion liquid of a fourth aspect of the present invention is the tin oxide particle dispersion liquid of any one of the first to third aspects, characterized in that the primary particle diameter of the tin oxide particles is within the range of 1.5 nm or more and 100 nm or less. According to the tin oxide particle dispersion liquid of aspect 4 of the present invention, the primary particle diameter of the tin oxide particles is within the range of 1.5 nm or more and 100 nm or less, so that a tin oxide particle laminated film with a thickness on the nano-order can be stably formed.
[0014] A method for producing a tin oxide particle laminate film according to a fifth aspect of the present invention is characterized by including a coating step of coating the tin oxide particle dispersion liquid according to any one of the first to fourth aspects. The method for producing a tin oxide particle laminate film according to aspect 5 of the present invention includes a coating step of coating the tin oxide particle dispersion liquid according to any one of aspects 1 to 4. This makes it possible to form a tin oxide particle laminate film in which the tin oxide particles are uniformly arranged and which has excellent electrical conductivity. Effect of the Invention
[0015] According to the present invention, it is possible to provide a tin oxide particle dispersion liquid capable of forming a tin oxide particle laminated film having excellent electrical conductivity in which tin oxide particles are uniformly arranged, and a method for producing a tin oxide particle laminated film. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a schematic explanatory diagram of a perovskite solar cell including a tin oxide particle laminate film according to an embodiment of the present invention. [Diagram 2] FIG. 1 is a flow diagram showing an example of a method for producing a tin oxide particle dispersion liquid according to an embodiment of the present invention. [Diagram 3] FIG. 1 is a flow diagram showing an example of a method for producing a tin oxide particle laminate film according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The following describes a tin oxide particle dispersion liquid and a method for producing a tin oxide particle laminate film according to embodiments of the present invention with reference to the accompanying drawings. Note that the following embodiments are specifically described to better understand the gist of the invention, and do not limit the present invention unless otherwise specified.
[0018] The tin oxide particle dispersion liquid according to an embodiment of the present invention is used, for example, when forming a tin oxide particle laminated film to be used as a conductive layer. The tin oxide particle laminate film according to an embodiment of the present invention is used, for example, as an electron transport layer of a perovskite solar cell shown in Fig. 1. A perovskite solar cell 10 has a structure in which an ITO film 12, an electron transport layer 13, a perovskite layer 14, a hole transport layer 15, and a back electrode 16 are laminated on the surface of a glass substrate 11, as shown in Fig. 1, for example.
[0019] The tin oxide particle laminated film constituting the electron transport layer 13 has a film thickness within the range of 10 nm to 100 nm. For this reason, in the tin oxide particle dispersion liquid of the present embodiment, it is required to form a thin and precise tin oxide particle laminate film. In addition, the tin oxide particle laminate film is required to have excellent conductivity as a conductive material.
[0020] The electrical conductivity of a tin oxide particle laminate film is greatly affected by the number of contacts between tin oxide particles in the tin oxide particle laminate film. Therefore, in order to improve electrical conductivity, the tin oxide particle laminate film needs to be formed so that the tin oxide particles are uniformly arranged. Therefore, in the tin oxide particle dispersion liquid of this embodiment, the zeta potential at pH 10 is set to −35 mV or less.
[0021] Here, we will explain the zeta potential. Metal oxides such as tin oxide have a surface potential when dispersed in water. In this aqueous dispersion of metal oxide, the potential of the slip surface where liquid flow begins in the electric double layer consisting of the ion fixed layer and ion diffusion layer formed around the metal oxide particles is called the zeta potential. The magnitude of this zeta potential depends on the surface condition of the metal oxide and the pH of the solution, and the zeta potential of tin oxide stabilizes at a pH of 10 or higher.
[0022] Here, a dispersion liquid in which tin oxide is dispersed in water usually has a zeta potential of about −35 mV to −25 mV at pH 10. In contrast, the tin oxide particle dispersion liquid of the present embodiment is configured so that the zeta potential at pH 10 is relatively low, at −35 mV or less, as described above. In this way, by setting the zeta potential at pH 10 low, the electrical repulsion between the tin oxide particles suppresses the aggregation of the tin oxide particles, resulting in uniform dispersion. Therefore, even if the dispersant volatilizes during the heating process of the applied tin oxide particle dispersion and the liquid becomes closer to neutral, the tin oxide particles will disperse without agglomerating, even without the use of a non-volatile dispersant, making it possible to apply a uniform film.
[0023] In the tin oxide particle dispersion liquid of this embodiment, the tin oxide particles may be doped with a different element other than Sn and O. The content of the different element is preferably within a range of 10,000 massppm to 100,000 massppm. As the different doping elements, it is preferable to use one or more elements selected from antimony, fluorine and phosphorus.
[0024] Furthermore, in the tin oxide particle dispersion liquid of this embodiment, the primary particle diameter of the tin oxide particles is preferably within the range of 1.5 nm or more and 100 nm or less. The primary particle size of the tin oxide particles is more preferably 1.8 nm or more, and even more preferably 2.0 nm or more, and more preferably 50 nm or less, and even more preferably 10 nm or less.
[0025] Next, an example of a method for producing a tin oxide particle dispersion liquid according to this embodiment will be described with reference to the flow diagram of FIG.
[0026] (Raw material suspension production process S01) A water-soluble alkali metal stannate (potassium stannate trihydrate in this embodiment) is dissolved in ion-exchanged water as a tin raw material to generate a base solution. An acid solution is added dropwise to this base solution and allowed to stand to generate a raw material suspension. In this raw suspension production step S01, it is preferable to mix while stirring at a dropping speed in the range of 15 mL / min to 100 mL / min. By increasing the mixing speed of the acid solution and the base solution (increasing the dropping speed, stirring with a stirrer or vortex mixer during mixing, or mixing the liquids in a flow path using a jet flow), it becomes possible to arrange stannate ions (derived anions) on the particle surface. In addition, it is preferable to set the standing time in the range of 1 day to 14 days.
[0027] (Raw material liquid generation process S02) Next, ammonia water is added to the obtained raw material suspension to produce a raw material liquid. In this raw material liquid producing step S02, the ammonia concentration in the ammonia water to be added is preferably set within the range of 0.2 mass % to 28 mass %.
[0028] (Synthesis step S03) Next, the above-mentioned raw material liquid is placed in a sealed container and subjected to a heat treatment to produce a tin oxide particle dispersion liquid. Here, it is preferable that the synthesis temperature T in the synthesis step S03 is within a range of 20° C. or more and 280° C. or less, the reaction time H is within a range of 0.1 hours or more and 120 hours or less, and the product T×H of the synthesis temperature T and the synthesis time H is within a range of 20 or more and 8000 or less.
[0029] The above-described steps form a tin oxide particle dispersion liquid according to the present embodiment. This tin oxide particle dispersion liquid has a zeta potential of −35 mV or less at pH 10.
[0030] Next, an example of a method for producing a tin oxide particle laminated film using the tin oxide particle dispersion liquid according to this embodiment will be described with reference to the flow diagram of FIG.
[0031] (Solid concentration adjustment step S11) First, a tin oxide particle dispersion liquid according to this embodiment is prepared, and the solid content concentration in the tin oxide particle dispersion liquid is adjusted using ion-exchanged water so as to be within the range of 2 mass % or more and 20 mass % or less. The solid content concentration in the tin oxide particle dispersion liquid is preferably 5 mass% or more, more preferably 8 mass% or more, and is preferably 18 mass% or less, more preferably 15 mass% or less.
[0032] (Coating process S12) Next, the tin oxide particle dispersion liquid with the adjusted solid content concentration is applied onto a substrate by a spin coater. The conditions for the spin coating in the coating step S12 are preferably a rotation speed in the range of 500 rpm to 3000 rpm, a coating time in the range of 5 seconds to 60 seconds, and a thickness of the coating film in the range of 20 nm to 100 nm.
[0033] (Heating process S13) Next, the coating film (the coated tin oxide particle dispersion liquid) is heated to remove the solvent, thereby forming a tin oxide particle laminate film. The heating conditions in this heating step S13 are preferably a heating temperature in the range of 100° C. to 400° C. and a heating time in the range of 1 minute to 10 minutes.
[0034] Through the above-described steps, the tin oxide particle laminate film of this embodiment is formed. Here, in the tin oxide particle laminate film of this embodiment, the average film thickness is in the range of 10 nm to 100 nm, the standard deviation of the film thickness is in the range of 3 nm to 40 nm, and the coefficient of variation of the film thickness CV is 50% or less.
[0035] According to the tin oxide particle dispersion liquid of the present embodiment configured as described above, the zeta potential at pH 10 is suppressed to a low level of -35 mV or less, so that when this tin oxide particle dispersion liquid is applied, the tin oxide particles are uniformly dispersed without agglomeration. Therefore, even if the dispersant volatilizes when the coating film of the tin oxide particle dispersion liquid is heat-treated, the aggregation of the tin oxide particles is suppressed, and the tin oxide particles are uniformly arranged. In addition, there is no need to add a non-volatile dispersant, and the presence of the non-volatile dispersant between the tin oxide particles can be suppressed. This ensures a sufficient number of contact points between the tin oxide particles, making it possible to form a tin oxide particle laminated film having excellent electrical conductivity.
[0036] Furthermore, in the tin oxide particle dispersion liquid of the present embodiment, when the tin oxide particles are doped with a different element, it is possible to form a tin oxide particle laminate film according to the required characteristics depending on the type and content of the different element to be doped. Here, when the different element is one or more elements selected from antimony, fluorine and phosphorus, it is possible to form a tin oxide particle laminated film having particularly excellent electrical conductivity.
[0037] Furthermore, in the tin oxide particle dispersion liquid of this embodiment, when the primary particle diameter of the tin oxide particles is within the range of 1.5 nm or more and 100 nm or less, the tin oxide particles are uniformly dispersed, even when the tin oxide particle laminate film is formed with a thickness on the nano-order, and it is possible to stably form a tin oxide particle laminate film with a uniform thickness.
[0038] The method for producing a tin oxide particle laminate film of the present embodiment includes a coating step S12 of coating the tin oxide particle dispersion of the present embodiment, so that the tin oxide particles are uniformly arranged, making it possible to form a tin oxide particle laminate film having excellent electrical conductivity.
[0039] Although one embodiment of the present invention has been described above, the present invention is not limited to this embodiment, and can be modified as appropriate without departing from the technical concept of the invention. In this embodiment, the tin oxide particle laminated film has been described as constituting the electron transport layer of the perovskite solar cell shown in FIG. 1, but it may be used for other purposes without being limited thereto. EXAMPLES
[0040] A confirmation experiment conducted to confirm the effectiveness of the present invention will be described.
[0041] (Example of the present invention) In the present invention, potassium stannate trihydrate was used as the tin source (base source). 1.99 g of potassium stannate trihydrate was dissolved in 10 g of ion-exchanged water to obtain a base solution. An acid solution containing the acid raw material shown in Table 1 was added dropwise to this base solution at a rate of 1 mL / min, and the solution was allowed to stand for 3 days to obtain a raw material suspension. To the raw material suspension, 7.0 g of 1.4 mass % ammonia water was added to prepare a raw material liquid. This raw material liquid was placed in a sealed container and heated under the synthesis conditions shown in Table 1 to obtain a tin oxide particle dispersion liquid.
[0042] In Example 10 of the present invention, 0.180 g of antimony (III) chloride was added to the basic solution, and then the acid solution was added dropwise to the basic solution to dope it with Sb. In Example 11 of the present invention, 0.108 g of phosphorus trichloride was added to the basic solution, and then the acid solution was added dropwise to the basic solution to dope it with P. Furthermore, in Inventive Example 12, 0.025 g of tin (IV) fluoride was added to the base solution, and then the acid solution was added dropwise to the base solution to dope it with F. In addition, in Example 13 of the present invention, 0.180 g of antimony chloride (III) and 0.108 g of phosphorus trichloride were added to the basic solution, and then an acid solution was added dropwise to the basic solution to dope F and P.
[0043] (Comparative Example) In the comparative example, tin(IV) chloride pentahydrate was used as the tin raw material (acid raw material). 1.80 g of tin(IV) chloride pentahydrate was dissolved in 5.2 g of ion-exchanged water to obtain an acid solution. A base solution containing the base raw material shown in Table 1 was added dropwise to this acid solution at a rate of 1 mL / min, and the solution was allowed to stand for 3 days to obtain a raw material suspension. To the raw material suspension, 7.0 g of 1.4 mass % ammonia water was added to prepare a raw material liquid. This raw material liquid was placed in a sealed container and heated under the synthesis conditions shown in Table 1 to obtain a tin oxide particle dispersion liquid.
[0044] (Tin oxide particle laminated film) The above-mentioned tin oxide particle dispersion liquid was diluted with ion-exchanged water to a solid content concentration of 8 mass %. The diluted tin oxide particle dispersion liquid was spin-coated on a 50 mm×50 mm glass substrate using a spin coater (Mikasa Co., Ltd., model number: MS-A150) at 500 rpm for 60 seconds to form a coating film. The glass substrate on which the coating film was formed was heated on a hot plate at 100° C. for 3 minutes to form a tin oxide particle laminate film.
[0045] The tin oxide particle dispersion liquid and the tin oxide particle laminated film obtained as described above were evaluated for each item by the following methods. The evaluation results are shown in Table 1.
[0046] (Zeta potential) The tin oxide dispersion was diluted to 1.0 mass% with ion-exchanged water, and then 0.1 mol / L hydrochloric acid was added to adjust the pH to 10.0. This was used as a sample and the zeta potential was measured using a particle size distribution measuring device (Malvern Zetasizer nano). The measurement was performed three times, and the average value was taken as the zeta potential value at pH 10.
[0047] (Primary particle size of tin oxide particles) The tin oxide particles dispersed in the solvent were photographed at a magnification of 200,000 times using a transmission electron microscope (JEOL Ltd., model number: JEM-2010F). The particle diameters of 100 particles were measured from the photographed image using software (product name: Image J), and the average was calculated.
[0048] (Conductivity of tin oxide particle laminated film) The resistance of the tin oxide particle laminated film obtained as described above was measured using a surface resistance measuring device (product number: Loresta AP MCP-T400, probe: ASP probe (four-needle), manufactured by Mitsubishi Chemical Corporation).
[0049] [Table 1]
[0050] In Comparative Example 1, the zeta potential at pH 10 was −31.8 mV, and the electrical resistance of the tin oxide particle laminated film was 6.31×10 7 The value was high at Ω, indicating poor electrical conductivity. In Comparative Example 2, the zeta potential at pH 10 was −33.8 mV, and the electrical resistance of the tin oxide particle laminate film was 4.18×10 7 The value was high at Ω, indicating poor electrical conductivity.
[0051] In contrast, in Examples 1 to 13 of the present invention, the zeta potential at pH 10 was −35 mV or less, and the electrical resistance of the tin oxide particle laminate film was 9.44 × 10 6 The value was low at Ω or less, indicating excellent conductivity.
[0052] As described above, it has been confirmed that the present invention can provide a tin oxide particle dispersion capable of forming a tin oxide particle laminate film having excellent electrical conductivity in which the tin oxide particles are uniformly arranged, and a method for producing a tin oxide particle laminate film.
Claims
1. A tin oxide particle dispersion liquid in which tin oxide particles are dispersed in a solvent, A tin oxide particle dispersion liquid having a zeta potential at pH 10 of -35 mV or less.
2. 2. The tin oxide particle dispersion according to claim 1, wherein the tin oxide particles are doped with a different element.
3. 3. The tin oxide particle dispersion liquid according to claim 2, wherein the different element is one or more elements selected from the group consisting of antimony, fluorine and phosphorus.
4. 2. The tin oxide particle dispersion liquid according to claim 1, wherein the primary particle diameter of the tin oxide particles is within a range of 1.5 nm to 100 nm.
5. A method for producing a tin oxide particle laminate film, comprising the steps of: A method for producing a tin oxide particle laminate film, comprising: a coating step of coating the tin oxide particle dispersion liquid according to claim 1 .
Citation Information
Patent Citations
Spin coating
JP1989027667A